IPTEKS SISTEM PELAPORAN AKUNTANSI BANK INDONESIA - Sigar, Preisia; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
Bank Indonesia is the Central Bank. The Central Bank is the center of monetary policy and monetary stability in Indonesia. As a Central Bank certainly has a system in accounting reporting. Based on research conducted at BI and existing discussions, the conclusion that can be taken is that BI adheres to the system issued by the Bank Indonesia Accounting Policy (KAKBI) based on the Bank Indonesia Governor Regulation (PDGBI). Suggestion that BI continues to improve transparency and accountability so that the quality of bank Indonesia reporting system information is accurate and reliable. Keywords: accounting system, repportimg